2018
DOI: 10.1002/nau.23709
|View full text |Cite
|
Sign up to set email alerts
|

Do we understand voiding dysfunction in women? Current understanding and future perspectives: ICI‐RS 2017

Abstract: In the future, recommendations for research should lead to a better understanding of urinary retention in women and its treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 90 publications
0
28
0
Order By: Relevance
“…The terms and phrases used included 'female' combined with 'voiding dysfunction', 'urinary retention', 'detrusor underactivity', 'Fowler's syndrome', 'high-tone nonrelaxing sphincter', 'urethral stricture', 'bladder neck obstruction', 'dysfunctional voiding' and 'idiopathic chronic urinary retention'. In addition, aspects of the existing guidance from the European Association of Urology [4] and a publication from the relevant International Consultation on Incontinence Research Society 'Think Tanks' (ICI-RS) [5] were used, and further informed by UK best practice, to provide a framework for assessment, investigation and management of these patients.…”
Section: Methodsmentioning
confidence: 99%
“…The terms and phrases used included 'female' combined with 'voiding dysfunction', 'urinary retention', 'detrusor underactivity', 'Fowler's syndrome', 'high-tone nonrelaxing sphincter', 'urethral stricture', 'bladder neck obstruction', 'dysfunctional voiding' and 'idiopathic chronic urinary retention'. In addition, aspects of the existing guidance from the European Association of Urology [4] and a publication from the relevant International Consultation on Incontinence Research Society 'Think Tanks' (ICI-RS) [5] were used, and further informed by UK best practice, to provide a framework for assessment, investigation and management of these patients.…”
Section: Methodsmentioning
confidence: 99%
“…According to the International Continence Society (ICS) recommendations [ 15 ], a bladder outflow obstruction due to overactive urethral function during voiding (dysfunctional voiding) is considered when all the following parameters are observed: a maximum flow rate < 15 ml/s; a maintained detrusor contraction (> 25 cmH 2 O) in the presence of incomplete bladder emptying (post-voided volume > 100 ml and voided volume > 200 ml); an increase in EUS EMG activity during micturition [ 16 ]. Bladder acontractility was diagnosed when a complete absence of detrusor pressure waves was observed on pressure-flow studies (PFS), regardless of the post-voided residual and maximum flow rate.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to DO, bladder outlet obstruction (BOO) may play a role in the development of OAB, because OAB and voiding dysfunction (VD) can coexist 7,8 . VD, which is de ned as abnormally slow and/or incomplete micturition, can be classi ed as BOO (mechanical and functional) and detrusor underactivity (DU) 9,10 . In a comprehensive review, Fusco et al reported that DO during the lling phase is the compensation phase of BOO-induced bladder remodeling 11 .…”
Section: Introductionmentioning
confidence: 99%